2021
DOI: 10.3390/ijerph18189798
|View full text |Cite
|
Sign up to set email alerts
|

When Do Hedonic and Eudaimonic Orientations Lead to Happiness? Moderating Effects of Orientation Priority

Abstract: The effects of hedonic and eudaimonic orientations on individual well-being have received much scholarly attention. However, the empirical findings from previous research are not consistent, raising the question of when the pursuit of hedonia and eudaimonia lead to actual improvements in individual well-being. We argue that the relationship between orientations to happiness and well-being outcomes are moderated by orientation priorities, which reflect the relative level of importance individuals place on eudai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The full life hypothesis ( Peterson et al, 2005 ; Huta and Ryan, 2010 ), which posits that both pursuing hedonia and eudaimonia are related to an increase in actual well-being, was not fully supported in the current study. Instead, in accordance with some recent studies ( Sheldon et al, 2019 ; Lin and Chan, 2020 ; Chen and Zeng, 2021 ), our findings suggested that the pursuit of hedonia could be related to a decrease in individuals’ well-being. More importantly, this study expands previous research by extending the negative outcomes of hedonia from subjective experience to objective functioning.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The full life hypothesis ( Peterson et al, 2005 ; Huta and Ryan, 2010 ), which posits that both pursuing hedonia and eudaimonia are related to an increase in actual well-being, was not fully supported in the current study. Instead, in accordance with some recent studies ( Sheldon et al, 2019 ; Lin and Chan, 2020 ; Chen and Zeng, 2021 ), our findings suggested that the pursuit of hedonia could be related to a decrease in individuals’ well-being. More importantly, this study expands previous research by extending the negative outcomes of hedonia from subjective experience to objective functioning.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Klipker et al (2017) found that when confronted with daily hassles, hedonic orientation was negatively related to affective well-being in adolescents with low cognitive control; however, for adolescents with high cognitive control, strong hedonic orientation was related to improved affective well-being. In another study, Chen and Zeng (2021) demonstrated the moderating role of orientation priority. This refers to the relative importance placed on eudaimonic goals over hedonic ones, in the relationship between happiness orientation and individual well-being.…”
Section: Discussionmentioning
confidence: 91%
“…Hedonic Motive refers to the enjoyment or pleasure of customers derived from using technology (Venkatesh et al, 2012). The hedonic motive is meant to seek pleasure and comfort (Chen & Zeng, 2022). It shows a willingness to initiate behaviors that result in improved positive experiences or decreased negative experiences (Kaczmarek, 2017).…”
Section: Hedonic Motive (Hm)mentioning
confidence: 99%